Spatial price transmission and market intergration analysis : the case of wheat market in South Africa, 2010-2019 - Mphateng, Molahlegi Aubrey (My University, 2022)
Wheat forms part of the most essential grain crop produced in South Africa after maize. In South Africa, most of the wheat produced is used mainly for human consumption while the remaining is used for animal feed and seed. The wheat industry in South Africa is undergoing severe pressure, with drastic decreases in the area planted to wheat production while imports of wheat continued to increase since the year 1997. This has in return affected the performance and competitiveness of the South African wheat industry at the international stage and its ability to produce enough to meet local demand, hence continuous reliance on imports which later affect domestic wheat prices. Regardless of wheat as one of the most essential grain crop produced in South Africa, very little research is done to evaluate the co-movement, magnitude and speed of price transmission from world to domestic wheat market in South Africa. The study intends to analyse the transmission of world wheat prices to the domestic wheat market in South Africa using average weekly prices for wheat for the period between January 2010 and December 2019. The objectives of the study are to determine the level of cointegration or long run relationship between the world wheat prices and the domestic wheat prices in South Africa, and to assess the degree of world wheat price transmission to the domestic wheat prices in South Africa, with the application of the Error Correction Model. While several authors indicted that long run relationship does exist between spatially separated markets, this study also finds evidence of cointegration or long run relationship between world wheat markets and the domestic wheat market in South Africa. The results confirmed this priori expectation, that in a long run world wheat prices are ultimately transmitted to the domestic market in South Africa. The results further indicate that the speed of corrections or adjustments towards equilibrium conditions were established to be fairly low for domestic wheat prices. The study recommends further research with more emphasis on vertical price transmission from wheat to wheat flour and other wheaten products such as bread and cereals. Further recommendation suggested by the study is that government intervention through implementation of Dollar-Based Reference Price and Variable Tariff Formula for wheat must continue with more caution and improved speed for a quicker response, once there is a newly triggered import duty.
Thesis (M.A. Agricultural Management (Agricultural Economics)) -- University of Limpopo, 2022
Keywords: Price transmission; Cointegration; Wheat tarif; Spatial price transmission; Spatial market efficiency; Spatial arbitrage; Wheat value chain; Price asymmetry; Wheat price; Wheat; Crops; Cointegration; Wheat trade